POLITICAL MARKETING STURMAN PANJAITAN PADA PEMILIHAN UMUM LEGISLATIF TAHUN 2024 DI KOTA BATAM - Sibarani, Arauna Elkana; Nisaa, Fadhiilatun (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
he 2024 Legislative Elections show a growing trend in the use of political marketing strategies by legislative candidates. One interesting figure to analyze is Sturman Panjaitan, an incumbent legislative candidate from Batam City. Sturman not only relies on the strength of his formal political network but is also able to "sell" himself as a political product that is relevant and close to the community, particularly by utilizing a targeted and systematic approach to political marketing. This study aims to analyze the political marketing used by Sturman Panjaitan in winning the 2024 Legislative Elections in Batam City. The approach used in this study is a qualitative approach with descriptive methods. Data were collected through in-depth interviews and documentation of Sturman Panjaitan, his campaign team, volunteers, and voters. The main theory used is the 3P concept in political marketing: push marketing, pull marketing, and pass marketing. The results show that Sturman Panjaitan implemented these three strategies in an integrated manner. Push marketing was carried out through direct campaigning, distribution of campaign materials, and community meetings. Pull marketing was realized through positive imagery on social media and mass media, as well as campaign narratives that build emotional closeness with voters. Meanwhile, pass marketing is seen from the active role of volunteers and community networks in spreading political messages organically. Keywords: Campaign, Election of Legislative Members, Political Marketing